Answer:
![\displaystyle x=\pm (√(a(y - b)))/(a)](https://img.qammunity.org/2023/formulas/mathematics/high-school/l1uv8n79fjad9ofn34as2ka7vbp3bfjtuz.png)
Explanation:
To make x the subject of the formula, we will isolate the x variable by using inverse operations.
Given:
y = ax² + b
Subtract b from both sides of the equation:
ax² = y - b
Divide both sides of the equation by a:
x² =
![( y - b)/(a)](https://img.qammunity.org/2023/formulas/mathematics/high-school/68m8smuwvf2siyk6qw1bu5gwv1qn0v8tda.png)
Square root both sides of the equation and rewrite:
![\displaystyle x=\pm (√(a(y - b)))/(a)](https://img.qammunity.org/2023/formulas/mathematics/high-school/l1uv8n79fjad9ofn34as2ka7vbp3bfjtuz.png)